Heavy Metal Pollution in the Environment and Its Impact on Health: Exploring Green Technology for Remediation - Sumanta Das; Kaniz Wahida Sultana; Ashwell R Ndhlala; Moupriya Mondal; Indrani Chandra (SAGE Publishing, 2023)
Along with expanding urbanization and industrialization, environmental pollution which negatively affects the surroundings, has been rising quickly. As a result, induces heavy metal contamination which poses a serious threat to living organisms of aquatic and soil ecosystems. Therefore, they are a need to ameliorate the effects cost by cost pollution on the environment. In this review, we explore methods employed to mitigate the effects caused by heavy metals on the environment. Many techniques employed to manage environmental pollution are tedious and very costly, necessitating the use of alternative management strategies to resolve this challenge. In this concept, bioremediation is viewed as a future technique, due to its environmental friendliness and cost-effective measures aligned with sustainable or climate-smart agriculture to manage contaminants in the environment. The technique involves the use of living entities such as bacteria, fungi, and plants to deteriorate toxic substances from the rhizosphere. Currently, bioremediation is thought to be the most practical, dependable, environmentally benign, and long-lasting solution. Although bioremediation involves different techniques, they are still a need to find the most efficient method for removing toxic substances from the environment. This review focuses on the origins of heavy metal pollution, delves into cost-effective and green technological approaches for eliminating heavy metal pollutants from the environment, and discusses the impact of these pollutants on human health.